Produção de café sombreado - Mancuso, Mauricio Antonio Cuzato [UNESP]; Soratto, Rogério Peres [UNESP]; Perdoná, Marcos José (Associacao Prudentina de Educacao e Cultura (APEC), 2013)
As concern about the environment and demand for special coffees, this review aimed to gather information about the effects of shading on the coffee crop, whereas its origin in the African's understory. Among the effects discussed are the increase in organic matter and improving of the soil fauna, nutrient cycling, decrease of soil erosion, environmental contamination, greenhouse gases, biodiversity conservation, light availability, temperature and wind mitigation, incidence of pests, plant diseases and weeds, production of the shade species and, finally, how all of these factors together have an effect on the phenology, yield and quality of coffee.

Com a crescente preocupação ambiental e demanda por cafés especiais, a presente revisão teve como objetivo agregar informações a respeito dos efeitos causados pelo sombreamento sobre a cultura do café, visto que esta cultura é originária de sub-bosques africanos. Entre os efeitos abordados estão o aumento da matéria orgânica e melhoria da fauna do solo, ciclagem de nutrientes, redução dos processos erosivos no solo, contaminação ambiental, gases do efeito estufa, conservação da biodiversidade, disponibilidade luminosa, atenuação da temperatura e ventos, incidência de pragas, doenças e plantas daninhas, produção das espécies de sombreamento e, por fim, de que maneira todos esses fatores associados interferem na fenologia, produção e qualidade do café.
Shaded coffee production
Keywords: Intercropping; Special coffees; Arborization; Quality; Coffea sp.; Consorciação; Cafés especiais; Arborização; Qualidade